2012
DOI: 10.2174/1874375701206010001
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin, Angiotensin II and Tyrosine-Hydroxylase Expression in the Hypothalamus of the Syndrome of Inappropriate ADH: A Case Report

Abstract: Abstract:The Syndrome of Inappropriate Antidiuretic Hormone (SIADH) is a disease characterized by hyponatremia and hyperosmolality of urine, and where vasopressin, angiotensin II and catecholamines are implicated in salt water balance, cardiovascular and blood pressure regulation. Therefore, the aim of this study is to analyze the hypothalamic distribution of vasopressin (VAS) Angiotensin II (AGII) and tyrosine-hydroxylase (TH) in a case of SIADH and compare it with a case without SIADH. Two hypothalamus taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This increase depends on an excessive water intake that overwhelms the restricted renal ability of diluting urine and mounting compensatory diuresis due to vasopressin dysregulation. A previous work [20] showed that vasopressin immunoreactive material was less intensive and was present in a lower number of cells and fibres in the SIADH case where it was mainly found in the whole supraoptic nucleus and the magnocellular part of the paraventricular hypothalamic nucleus. The low intensity of VAS in the case of SIADH could mean an increase in VAS release owing to variations in the vasopressin receptor, since other studies [21] have described cases, whose clinical presentation and laboratory findings were consistent with SIADH but which exhibited unmeasurable VAS levels on repeated occasions that seems to be due to an activating mutation of the vasopressin receptor V2 (V2R).…”
Section: Discussionmentioning
confidence: 82%
“…This increase depends on an excessive water intake that overwhelms the restricted renal ability of diluting urine and mounting compensatory diuresis due to vasopressin dysregulation. A previous work [20] showed that vasopressin immunoreactive material was less intensive and was present in a lower number of cells and fibres in the SIADH case where it was mainly found in the whole supraoptic nucleus and the magnocellular part of the paraventricular hypothalamic nucleus. The low intensity of VAS in the case of SIADH could mean an increase in VAS release owing to variations in the vasopressin receptor, since other studies [21] have described cases, whose clinical presentation and laboratory findings were consistent with SIADH but which exhibited unmeasurable VAS levels on repeated occasions that seems to be due to an activating mutation of the vasopressin receptor V2 (V2R).…”
Section: Discussionmentioning
confidence: 82%